The ornamental calcite vessels from the tomb of Tutankhamun - MANNICHE L. (Griffith Institute publications.)
"At the time of the clearing of the tomb of Tutankhamun Howard Carter and his team made meticulous handwritten notes of every single object found. Yet a full scholarly publication of the majority of them has yet to be undertaken. This book presents a catalogue of the ornamental calcite vessels with an introduction and a discussion of their artistic merit, at times disputed, as well as their purpose during the life of Tutankhamun and after his death. Most of them were designed to contain scented unguents so precious that they proved irresistible to robbers in antiquity. Their intricate design combining utilitarian use with symbolic forms and ornamentation paired with a near perfect state of preservation makes them rare examples of royal arts and crafts of late 18th dynasty Egypt. The book is illustrated with original black & white photographs, most of them taken at the time of the discovery by Harry Burton, as well as some drawings made by Howard Carter. The colour photographs are by Sandro Vannini."--Publisher's website.